Community Empowerment Through Potato Crispy Home Industry to Increase Added Value of Agricultural Products in Ria-Ria Village, Pollung District, Humbang Hasundutan Regency - Lubis, Muhammad Arif; Silalahi, Amlys Syahputra; Hutagalung, Arif Qaedi (Talenta Publisher, 2022)
The agricultural sector is an important sector for economic development. In accordance with the Nawa Cita, the government prioritizes the direction of development in the agricultural sector to support the realization of food sovereignty so that Indonesia as a nation can regulate and meet the food needs of its people sovereignly. Humbang Hasundutan Regency, where most of the population lives from the agricultural sector, is one of the target areas for the development of agricultural areas in Indonesia and is one of the locations for the Food Estate area which is one of the strategic programs for national agricultural development in 2021. Farmer corporation development is a priority so that farmers control production. and agricultural business from upstream to downstream. The assistance process in the context of community empowerment must be carried out in farmer corporations. Farmers must be able to create added value agricultural products. The greater added value of agricultural products can certainly play a role in increasing economic growth. Great economic growth, of course, has an impact on increasing business fields and people's incomes, which in the end is improving people's welfare.